Single-cell sequencing of immune cells from anticitrullinated peptide antibody positive and negative rheumatoid arthritis - Wu, Xunyao; Liu, Yi; Jin, Shanzhao; Wang, Min; Jiao, Yuhao; Yang, Bo; Lu, Xin; Ji, Xin; Fei, Yunyun; Yang, Huaxia; Zhao, Lidan; Chen, Hua; et al. (Nature communications, 2021)
The presence or absence of anti-citrullinated peptide antibodies (ACPA) and associated disparities in patients with rheumatoid arthritis (RA) implies disease heterogeneity with unknown diverse immunopathological mechanisms. Here we profile CD45 + hematopoietic cells from peripheral blood or synovial tissues from both ACPA+ and ACPA- RA patients by single-cell RNA sequencing and identify subsets of immune cells that contribute to the pathogenesis of RA subtypes. We find several synovial immune cell abnormalities, including up-regulation of CCL13 , CCL18 and MMP3 in myeloid cell subsets of ACPA- RA compared with ACPA+ RA. Also evident is a lack of HLA-DRB5 expression and lower expression of cytotoxic and exhaustion related genes in the synovial tissues of patients with ACPA- RA. Furthermore, the HLA-DR15 haplotype ( DRB1 / DRB5 ) conveys an increased risk of developing active disease in ACPA+ RA in a large cohort of patients with treatment-naive RA. Immunohistochemical staining shows increased infiltration of CCL13 and CCL18-expressing immune cells in synovial tissues of ACPA- RA. Collectively, our data provide evidence of the differential involvement of cellular and molecular pathways involved in the pathogenesis of seropositive and seronegative RA subtypes and reveal the importance of precision therapy based on ACPA status. Patients with rheumatoid arthritis are commonly stratified by ACPA serology, with positivity being associated with more severe disease and joint destruction. Here the authors present a single cell RNA sequencing resource comparing peripheral blood and synovial tissue cells from patients with ACPA+ versus ACPA- rheumatoid arthritis.